Prevalence and associated factors of antenatal depression in rural Bangladesh - Rifa Tamanna Mumu; Dipak Kumar Mitra; Md Parvez Shaikh (PLoS ONE, 2025)
Background According to the World Health Organization (WHO), approximately 322 million individuals all over the world suffered from depressive disorders in 2015. The risk of depression increases in pregnancy due to certain hormonal changes in the body. Despite the severe impacts of antenatal depression on both maternal and infant health, research on this issue remains limited in Bangladesh. Objective To identify the prevalence and associated factors of antenatal depression in rural Bangladesh. Method A cross-sectional study was conducted from January 08 to January 14, 2024, in Lohagara, a rural subdistrict of Narail in southern Bangladesh. The study recruited 350 pregnant women in different trimesters who attended antenatal checkups at a government health complex and a private hospital. Data was collected by face-to-face interviews using the Bengali-translated version of the Edinburgh Postnatal Depression Scale (EPDS) and another structured questionnaire. Pearson’s chi-square test, bivariate, and multivariate logistic regression were conducted to identify associated factors. Data were analyzed using STATA version 14. Result The point prevalence of antenatal depression was 39% (38.9%, 95% CI = 33.9% to 44%). Gestational week (AOR = 0.4, 95% CI = 0.2, 0.8), unintended pregnancy (AOR = 1.7, 95% CI = 1, 3), intimate partner violence (AOR = 3.3, 95% CI = 1.1, 9.7), a history of previous diseases (AOR = 2.4, 95% CI = 1.1, 5.2), and having polygamous husbands (AOR = 13.6, 95% CI = 1.1, 164) were found significantly associated with the development of depression in pregnancy. Conclusion The high prevalence of prenatal depression in rural Bangladesh highlights the urgent need for effective intervention. Raising awareness among healthcare professionals and families of pregnant women is essential to reducing its impact. Strategic planning and policymaking are necessary to address underlying social issues such as polygamy and intimate partner violence. Additionally, providing enhanced counseling and care for women with unplanned pregnancies or pre-existing health conditions is crucial for improving maternal mental well-being.